2015
DOI: 10.1016/j.apm.2015.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Two tuned multi-objective meta-heuristic algorithms for solving a fuzzy multi-state redundancy allocation problem under discount strategies

Abstract: a b s t r a c tIn this study, a bi-objective multi-state redundancy allocation problem of series-parallel systems consisting of some serial subsystems, each with non-repairable components in parallel, is investigated. Furthermore, due to uncertainty involved, both the performance rates and the availabilities of components are considered fuzzy. In addition, two strategies of allunit and incremental-quantity discounts are used to purchase the components and that the fuzzy universal generating function (FUGF) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…They showed that the algorithm performs better than the non-dominated sorting genetic algorithm II (NSGA-II). Mousavi et al 19 proposed a redundancy allocation problem under multi-state and bi-objective of series–parallel systems including some serial subsystems, based on which some non-repairable components were considered under a discount strategy. It should be mentioned that both the performance rates and the component reliability were considered fuzzy in their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that the algorithm performs better than the non-dominated sorting genetic algorithm II (NSGA-II). Mousavi et al 19 proposed a redundancy allocation problem under multi-state and bi-objective of series–parallel systems including some serial subsystems, based on which some non-repairable components were considered under a discount strategy. It should be mentioned that both the performance rates and the component reliability were considered fuzzy in their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The suggested algorithm is as follows: 1) Estimate the probability density function for carbon emission quotient In this paper, the centroid method is applied for the defuzzification of the trapezoidal fuzzy number. The centroid of the trapezoidal fuzzy number t u is shown in Equation 23 [47].…”
Section: Trcementioning
confidence: 99%
“…[35]2015BinaryHeteroGA, MASingleRSMTime-dependentMousavi et al. [36]2015MultiHomosCE-NRGAMultipleTaguchiConstantZaretalab et al. [37]2015MultiHomosMOSAMultiple-ConstantCurrent Research---MultiHomosNSGA-II/NRGASingleRSMConstant…”
Section: Introductionmentioning
confidence: 99%